Epitaph of a Small Winner: My First 50 Years in Academe. An Interview with Judith Ewell. Issue 2 (18th April 2018) - Lane, Kris
Abstract : Judith Ewell has been a major figure in modern Latin American history, both as a research scholar and as a teacher. Just before receiving her PhD at the University of New Mexico in 1972, Ewell began teaching at the College of William & Mary in Williamsburg, Virginia, from which she retired in 2004. Ewell's books include The Indictment of a Dictator: The Extradition and Trial of Marcos Pérez Jiménez (1981); Venezuela: A Century of Change (1984); and Venezuela and the United States: From Monroe's Hemisphere to Petroleum's Empire (1996, Spanish ed. 1998). Ewell has also published numerous articles and book chapters on modern Latin American history and women's history. She is co-editor of the much-loved biographical essay collection, The Human Tradition in Latin America (Nineteenth and Twentieth Centuries) with William H. Beezley, with whom she served on the editorial board of Scholarly Resources Press (now Rowman & Littlefield). Most importantly, Ewell served as chief editor of this journal, The Americas, from 1998 to 2003.